In-situ simulation-based team training reduces incidence of negative events during bronchoscopy. A prospective educational intervention cohort study - Andreas Fosli Clausen; Søren Sperling; Rune Dall Jensen; Søren Helbo Skaarup (Respiratory Research)
Abstract Introduction While bronchoscopy complications are rare, they can be life-threatening if not quickly managed. This study evaluates the effect of a case-based bronchoscopy simulation training using real-world data on complication incidence and nature. Methods Based on semi structured interviews with respiratory staff in a bronchoscopy unit a team simulation training case was constructed. It was assessed using the Kirkpatrick framework to measure changes in procedural behavior by the rate of adverse events (level three) as the main outcome. Participants’ reactions, changes in stress levels, and patient perspectives (levels one, two, and four) were evaluated via questionnaires. Results Following the educational intervention, the incidence of any negative events during bronchoscopies was reduced from 62% (38/61) to 41% (26/63), p = 0.019. The most frequent event was oxygen desaturation below 90%, which occurred in 34% of the bronchoscopies before the intervention vs. 11% afterwards, p = 0.002. The participants found the simulation-based training relevant but did not change the perceived level of stress. The patient reported to be less awake (2, IQR 1–5, vs. 5, IQR 3–8), p = 0.02 after the intervention. Conclusion Incorporation of in-situ simulation-based team-training for crisis management during bronchoscopy alter procedural behavior and significantly reduce the occurrence of adverse events; therefore, it should be integrated into future bronchoscopy training curricula.